Examining Factors of Sports Brand Logo Design that Influence Purchase Intentions : Undergraduate Students Perspective - Sin, Kit Yeng (Human Resource Management Academic Research Society, 2021)
Logo is vital for a company as it plays the huge role for the growth of business. Every company owner needs and desires their organization to be recognisable and boost the profit of company well. To achieve an impressive success in this competitive and challenging market, they must be one step ahead of their competitors. Thus, a company's meaningful logo can have a major effect on the market and attract new customers to boost revenue. As logo is the essentially branding tool, it is a company's or business's first point of communication and exposure with the world. This research study demonstrates the Signalling Theory which indicates the relationship between colour combination, shapes, lines and fonts used in logo towards purchase intention in sport’s brand product from University Malaysia Sarawak (Unimas) undergraduate students’ perspective. 374 questionnaires were distributed to respondents which are undergraduate students from Unimas for the purpose of testing and analysis of the hypotheses in this research study. The data collected was evaluated with the Statistical Package for the Social Sciences (SPSS) version 26.0. In this research, it was found that the shape of the logo and the line used in the logo had a major positive relationship with purchase intention towards sport brand product from Unimas undergraduate students’ perspective, while the colour combination of the logo and the font used in the logo had a minimal impact on purchase intention towards sport brand product among Unimas undergraduate students. In contrast, the relatively insignificant impact of colour combination and font used in logo on sport brand product implementation tended to be influenced by other variables that yet to be determined.